Wheat Germ Supplementation Improves Glucose Homeostasis Markers of Overweight Adults Independent of Gut Microbial Modulation. (7th June 2021) - Dotimas, Levin; Ojo, Babajide; Kaur, Amritpal; Alake, Sanmi; Dixon, Madison; Rassi, Guadalupe Davila-El; Zhao, Jiangchao; Ice, John; Emerson, Sam; Lucas, Edralin
Abstract: Objectives: This study investigated the effects of wheat germ (WG) supplementation on inflammation, metabolic, and gut health markers in overweight adults. Methods: Forty overweight (BMI = 25.0–30 kg/m 2 ) adults between 18–45 y old were recruited to this single-blinded randomized placebo-controlled study. Qualified participants were asked to maintain their normal diet and physical activity and consume energy balls containing 30 g of either WG or cornmeal (control) daily for 4 wks. Anthropometric and metabolic parameters, as well as dietary (3-d food record), medical history, physical activity (Yale Physical Activity Survey), stool measures (Bristol Stool Chart and the Cleveland Clinic Constipation Scoring System), gut integrity markers, and fecal bacterial population were assessed at baseline and at the end of the supplementation period. Results: Thirty-nine participants completed the 4-week study ( n = 20 and 19 for the WG and control group, respectively). There were no differences in the lipid profile, but glycated hemoglobin ( P = 0.04), insulin ( P = 0.03), and homeostatic model assessment of insulin resistance (HOMA-IR; P = 0.04) were significantly decreased in the WG but not the control group. Similarly, the adipokine resistin was also significantly reduced ( P = 0.03) by WG but not the control. There were no changes in stool characteristics between the two groups before and after supplementation. Similarly, there were no changes in gut bacterial population due to WG supplementation but the phyla Bacteroidetes ( P = 0.03) and Proteobacteria ( P = 0.048) and the genus Bacteroides ( P = 0.03) were significantly decreased in the control group. No significant changes were observed in plasma inflammatory markers, fecal short-chain fatty acid (SCFA) concentrations, and markers of gut integrity in both groups. Conclusions: Four weeks of WG supplementation improved markers of glucose homeostasis, which can partly be attributed to the reduction of the pro-inflammatory adipokine resistin and not due to changes within the gut (i.e., bacterial population, gut integrity markers, and SCFA production). Our findings indicate that WG may be a safe, effective, and economical approach to improve glucose homeostasis. Funding Sources: USDA Award #2019–67, 018-29, 260 and the Jim and Lynn Williams Professorship.